Implementation of two alcohol reduction interventions among persons with hazardous alcohol use who are living with HIV in Thai Nguyen, Vietnam: a micro-costing analysis. Issue 1 (31st December 2020) - Blackburn, Natalie A.; Go, Vivian F.; Bui, Quynh; Hutton, Heidi; Tampi, Radhika P.; Sripaipan, Teerada; Ha, Tran V.; Latkin, Carl; Golden, Shelley; Golin, Carol; Chander, Geetanjali; Frangakis, Constantine; et al.
ABSTRACT: Background: Hazardous alcohol use is detrimental to persons with HIV (PWH), impacting medication adherence and liver function, yet globally resources to target alcohol use behavior in this population are limited. Few studies have identified the costs of integrating alcohol reduction interventions into HIV care. Objective: To estimate the costs of implementing and delivering two evidence-based behavioral counseling interventions targeting hazardous alcohol use among persons with HIV and to estimate the costs of scale-up in ART clinics in Thai Nguyen, Vietnam. Methods: We undertook a micro-costing approach to determine the costs of delivering two adapted evidence-based interventions to reduce alcohol use: an intensive combined cognitive behavioral therapy and motivational enhancement therapy-informed intervention (CoI) and an abbreviated brief alcohol intervention (BI). A total of 294 participants with hazardous alcohol use were identified through a brief screening tool and received the CoI (n = 147) and the BI (n = 147) over 3 months. We estimated costs using time and motion studies, budget analysis, staff interviews, and participant questionnaires. Data were collected from 2016 to 2018 in VND and converted to USD. Results: The total cost of implementation and administration of the intervention to 147 participants receiving the CoI was 13, 900 (95 per participant) and to 147 participants receiving the BI was 5700 (39 per participant). Implementation and startup costs including training accounted for 27% of costs for the CoI and 28% for the BI. Counselor costs accounted for a large proportion of both the CoI (41%) and the BI (30%). Conclusions: Implementing and delivering alcohol reduction interventions to people with HIV in Vietnam with appropriate fidelity is costly. These costs may be reduced, particularly counselor labor costs, by using an evidence-based brief intervention format. Future research should explore the budgetary impact of brief and combined interventions to reduce hazardous alcohol use, particularly among vulnerable populations.